Earlier observations of presumed Galapagos sea lions, Zalophus californianus wollebaeki, from coastal Ecuador. - Palacios, D. M. (1996)
not in GAF
English
Keywords: Earlier observations of presumed Galapagos sea lions, Zalophus californianus wollebaeki, from coastal Ecuador. -- Galapagos sea lions, Zalophus californianus wollebaeki, sightings, Ecuador, coast -- Lobo marino, Galápagos, Zalophus californianus wollebaeki, observaciones, costa, Ecuador